2023
DOI: 10.3390/v15102073
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Conformational Dynamics and Systematic Characterization of Cryptic Pockets in the SARS-CoV-2 Omicron BA.2, BA.2.75 and XBB.1 Spike Complexes with the ACE2 Host Receptor: Confluence of Binding and Structural Plasticity in Mediating Networks of Conserved Allosteric Sites

Mohammed Alshahrani,
Grace Gupta,
Sian Xiao
et al.

Abstract: In the current study, we explore coarse-grained simulations and atomistic molecular dynamics together with binding energetics scanning and cryptic pocket detection in a comparative examination of conformational landscapes and systematic characterization of allosteric binding sites in the SARS-CoV-2 Omicron BA.2, BA.2.75 and XBB.1 spike full-length trimer complexes with the host receptor ACE2. Microsecond simulations, Markov state models and mutational scanning of binding energies of the SARS-CoV-2 BA.2 and BA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 145 publications
0
7
0
Order By: Relevance
“…75 The recent structural and computational studies suggested that Omicron mutations have significant and often variant-specific effect on mediating conformational dynamics changes in the S protein including allosterically induced plasticity at the remote regions leading to the formation and evolution of druggable cryptic pockets. 76,77 lineages proceeded through diverse mechanisms including but not limited to simple and complex recombination, antigenic drift and convergent evolution that led to convergent immune-escape mutations and effective evasion of neutralizing antibodies. 56 The recent proliferation of several lineages with similar replicative fitness and significant antigenic distance from each other was marked by the recent emergence of BA.…”
Section: Omicron Variantmentioning
confidence: 99%
“…75 The recent structural and computational studies suggested that Omicron mutations have significant and often variant-specific effect on mediating conformational dynamics changes in the S protein including allosterically induced plasticity at the remote regions leading to the formation and evolution of druggable cryptic pockets. 76,77 lineages proceeded through diverse mechanisms including but not limited to simple and complex recombination, antigenic drift and convergent evolution that led to convergent immune-escape mutations and effective evasion of neutralizing antibodies. 56 The recent proliferation of several lineages with similar replicative fitness and significant antigenic distance from each other was marked by the recent emergence of BA.…”
Section: Omicron Variantmentioning
confidence: 99%
“…Our recent studies combined multiscale simulations with network-based modeling to reveal that the S protein can function as a functionally adaptable allosterically regulated machine that exploits the plasticity of allosteric centers to fine-tune responses to antibody binding [41][42][43][44][45]. Recent computational studies in our laboratory also showed that SARS-CoV-2 S Omicron mutations have variant-specific effects on conformational dynamics changes including allosterically induced plasticity at the remote regions leading to the formation and evolution of druggable cryptic pockets [46,47].…”
Section: Introductionmentioning
confidence: 98%
“…67 Recent computational studies suggested that Omicron mutations have variant-specific effect on conformational dynamics changes in the S protein including allosterically induced plasticity at the remote regions leading to the formation and evolution of druggable cryptic pockets. 68,69…”
Section: Introductionmentioning
confidence: 99%